2016
DOI: 10.1104/pp.16.00881
|View full text |Cite
|
Sign up to set email alerts
|

The 5′UTR Intron of Arabidopsis GGT1 Aminotransferase Enhances Promoter Activity by Recruiting RNA Polymerase II

Abstract: Photorespiration is essential for the detoxification of glycolate and recycling of carbon to the Calvin Benson Bassham cycle. Enzymes participating in the pathway have been identified, and investigations now focus on the regulation of photorespiration by transporters and metabolites. However, regulation of photorespiration on the gene level has not been intensively studied. Here, we show that maximum transcript abundance of Glu:glyoxylate aminotransferase 1 (GGT1) is regulated by intron-mediated enhancement (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 66 publications
0
28
0
1
Order By: Relevance
“…The fact that the 5′UTR intron of GGT1 is able to drive leaf expression of both GGT2 and GLDP1-P2 as well as expression in trichomes of a root-specific PEROXIDASE (Laxa et al, 2016) might support the theory that expression is enhanced in a tissue in which expression is already determined but below the detection limit. Supporting this theory, Rose and Last (1997) showed that an increase in mRNA accumulation is depending on the presence of the AtPAT1 intron, while there was no change in the rate of transcription when compared to the intronless construct (Rose and Last, 1997).…”
Section: Ime Affects Multiple Levels Of Gene Expressionmentioning
confidence: 90%
See 4 more Smart Citations
“…The fact that the 5′UTR intron of GGT1 is able to drive leaf expression of both GGT2 and GLDP1-P2 as well as expression in trichomes of a root-specific PEROXIDASE (Laxa et al, 2016) might support the theory that expression is enhanced in a tissue in which expression is already determined but below the detection limit. Supporting this theory, Rose and Last (1997) showed that an increase in mRNA accumulation is depending on the presence of the AtPAT1 intron, while there was no change in the rate of transcription when compared to the intronless construct (Rose and Last, 1997).…”
Section: Ime Affects Multiple Levels Of Gene Expressionmentioning
confidence: 90%
“…In general, the impact of IME on transcription does not exceed two- to threefold (Rethmeier et al, 1997; Rose and Last, 1997; Furger et al, 2002; Samadder et al, 2008; Moabbi et al, 2012; Laxa et al, 2016). Thus, a significant difference in transcription that is mediated by an intron compared to an intronless control is even harder to detect than an increase in mRNA accumulation by 20-fold or more.…”
Section: Ime Affects Multiple Levels Of Gene Expressionmentioning
confidence: 99%
See 3 more Smart Citations